Outstanding Science Read-Alouds. - Salley, Coleen; Young Jr., Terrence E. (Book Links, 2004)
The article focuses on books related to science. According to standards set by the No Child Left Behind Act (NCLB), in the U.S. each state is required to create academic standards and proficiency levels in areas of math, reading, and science that all students must meet by 2014. Each state is also required to create a testing program to assess achievement. Science programs must institute required testing and measurements by the 2007-8 academic year. One benefit of NCLB mandatory science testing is that science resources will become increasingly important to the curriculum. INSETS: Web Connection;Series Connection.